Highly Porous Hybrid Metal–Organic Nanoparticles Loaded with Gemcitabine Monophosphate: a Multimodal Approach to Improve Chemo‐ and Radiotherapy. (17th December 2019) - Li, Xue; Porcel, Erika; Menendez‐Miranda, Mario; Qiu, Jingwen; Yang, Xiaomin; Serre, Christian; Pastor, Alexandra; Desmaële, Didier; Lacombe, Sandrine; Gref, Ruxandra
Abstract: Nanomedicine recently emerged as a novel strategy to improve the performance of radiotherapy. Herein we report the first application of radioenhancers made of nanoscale metal‐organic frameworks (nanoMOFs), loaded with gemcitabine monophosphate (Gem‐MP), a radiosensitizing anticancer drug. Iron trimesate nanoMOFs possess a regular porous structure with oxocentered Fe trimers separated by around 5 Å (trimesate linkers). This porosity is favorable to diffuse the electrons emitted from nanoMOFs due to activation by γ radiation, leading to water radiolysis and generation of hydroxyl radicals which create nanoscale damages in cancer cells. Moreover, nanoMOFs act as "Trojan horses", carrying their Gem‐MP cargo inside cancer cells to interfere with DNA repair. By displaying different mechanisms of action, both nanoMOFs and incorporated Gem‐MP contribute to improve radiation efficacy. The radiation enhancement factor of Gem‐MP loaded nanoMOFs reaches 1.8, one of the highest values ever reported. These results pave the way toward the design of engineered nanoparticles in which each component plays a role in cancer treatment by radiotherapy. Abstract : Cancer′s Trojan horse : Gemcitabine monophosphate (Gem‐MP), a radiosensitizing anticancer drug, was successfully loaded in iron trimesate nanoMOFs, which possess a porous structure with oxocentered Fe trimers separated by trimesate linkers. The radiation enhancement factor of Gem‐MP loaded nanoMOFs reaches 1.8, one of the highest values ever reported.